Five‐year risk of incident disease following a diagnosis of chronic rhinosinusitis. Issue 12 (25th September 2015) - Hirsch, A. G.; Yan, X. S.; Sundaresan, A. S.; Tan, B. K.; Schleimer, R. P.; Kern, R. C.; Kennedy, T. L.; Greene, J. S.; Schwartz, B. S.
Abstract: Background: Chronic rhinosinusitis (CRS) has a broad range of comorbidities. Due to a lack of longitudinal studies, it is not known whether these comorbidities cause CRS, are promoted by CRS, or share a systemic disease process with CRS. Objective: The objective of this study was to determine the risk of incident disease within 5 years after a new diagnosis of CRS with nasal polyps (CRSwNP) and without nasal polyps (CRSsNP). Methods: We conducted a case–control study nested within the longitudinal cohort of primary care patients in the Geisinger Clinic using electronic health record data. We evaluated incident disease over 5 years in newly diagnosed CRSwNP and CRSsNP cases compared to controls using multivariable Cox regression models. Results: CRSsNP ( n = 3612) cases were at greater risk (HR, 95% confidence interval) than controls for incidence of: upper airway diseases, including adenotonsillitis (3.29, 2.41–4.50); lower aerodigestive tract diseases, including asthma (2.69, 2.14–3.38); epithelial conditions, including atopic dermatitis (2.75, 1.23–6.16); and hypertension (1.38, 1.19–1.61). CRSwNP ( n = 241) cases were at greater risk for obesity than controls (1.74, 1.08–2.80), but CRSwNP was not associated with other diseases. Conclusion: The risk of other diseases associated with CRS adds to the burden of an already highly burdensome condition, and suggests either that CRS promotes onset of other diseases or is an indicator of systemic disease processes. Different patterns of association with diseases by CRS phenotype may be due to CRSwNP sample size limitations or reflect a different pattern of disease onset by phenotype. These findings have implications for screening guidelines and care of CRS patients.